2001
DOI: 10.1021/np010319c
|View full text |Cite
|
Sign up to set email alerts
|

Vidalenolone, a Novel Phenolic Metabolite from the Tropical Red Alga Vidalia sp.

Abstract: The Indonesian red alga Vidalia sp. was identified as a candidate for fractionation because its crude lipid extract showed activity in a mechanism-based anticancer assay (Fyn SH2-inhibitory activity). A chemically novel phenolic metabolite, vidalenolone, as well as two previously described and structurally simple phenols, were isolated as SH2-inactive substances. Their structures were determined by an interplay of spectroscopic methods, principally 2D NMR, and reference to literature data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…Liquiritigenin and 6-aldehydo-isoophiopogonone had been extracted earlier from Glycyrrhiza radixand Ophiopogon japonicas plants. Studies on these fractions reported Liquiritigenin and 6-aldehydo-isoophiopogononeto hold potent antioxidant, anti-allergic, anti-inflammatory, and anti-hyperlipidemic properties [49,50]. Likewise, Genistien-d 4 -an isoflavone and Vitexin -an epigenin flavone isolated from G. asiatica extracts had been reported to possess anti-inflammatory and anticancer properties against colon and breast cancer cells [51,52].Biological properties of G. asiatica fruit extracts reported in this study correlate with isolated bioactive compounds that had already been reported as potential antioxidant, anti-inflammatory and anti-cancerous agents.…”
Section: Identification Of Compounds By Lc-ms/msmentioning
confidence: 99%
“…Liquiritigenin and 6-aldehydo-isoophiopogonone had been extracted earlier from Glycyrrhiza radixand Ophiopogon japonicas plants. Studies on these fractions reported Liquiritigenin and 6-aldehydo-isoophiopogononeto hold potent antioxidant, anti-allergic, anti-inflammatory, and anti-hyperlipidemic properties [49,50]. Likewise, Genistien-d 4 -an isoflavone and Vitexin -an epigenin flavone isolated from G. asiatica extracts had been reported to possess anti-inflammatory and anticancer properties against colon and breast cancer cells [51,52].Biological properties of G. asiatica fruit extracts reported in this study correlate with isolated bioactive compounds that had already been reported as potential antioxidant, anti-inflammatory and anti-cancerous agents.…”
Section: Identification Of Compounds By Lc-ms/msmentioning
confidence: 99%
“…A chemically synthesized novel phenolic metabolite, vidalenolone, as well as two previously described and structurally simple phenols were isolated as SH2-inactive substances. Their structures were determined by spectroscopic methods such as 2D NMR [67]. The cytotoxic activities of all the synthetic compounds were determined against DLD-1 cells using the MTT assay.…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites have played an important role in leading to new pharmaceutical compounds for antitumor drugs (Luesch et al, 1999;Patterson et al, 1994;Yoo et al, 2002). Several representative antitumor compounds from algae, such as Halomon, had been developed to the clinical phase (Egorin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%